To expand the expression \(-\frac{5}{6}(9b - 12)\), you distribute \(-\frac{5}{6}\) to both terms inside the parentheses.
-
Distribute \(-\frac{5}{6}\) to \(9b\): \[ -\frac{5}{6} \times 9b = -\frac{5 \times 9b}{6} = -\frac{45b}{6} = -\frac{15b}{2} \]
-
Distribute \(-\frac{5}{6}\) to \(-12\): \[ -\frac{5}{6} \times -12 = \frac{5 \times 12}{6} = \frac{60}{6} = 10 \]
Now, putting both results together: \[ -\frac{5}{6}(9b - 12) = -\frac{15b}{2} + 10 \]
So, the expanded expression is: \[ -\frac{15b}{2} + 10 \]
You can fill in the blanks accordingly:
\(-\frac{15b}{2} + 10\)